Synthesis of the sulfur amino acids: cysteine and methionine - Wirtz, Markus; Droux, Michel (Photosynthesis research, 2005)
This review will assess new features reported for the molecular and biochemical aspects of cysteine and methionine biosynthesis in Arabidopsis thaliana with regards to early published data from other taxa including crop plants and bacteria (Escherichia coli as a model). By contrast to bacteria and fungi, plant cells present a complex organization, in which the sulfur network takes place in multiple sites. Particularly, the impact of sulfur amino-acid biosynthesis compartmentalization will be addressed in respect to localization of sulfur reduction. To this end, the review will focus on regulation of sulfate reduction by synthesis of cysteine through the cysteine synthase complex and the synthesis of methionine and its derivatives. Finally, regulatory aspects of sulfur amino-acid biosynthesis will be explored with regards to interlacing processes such as photosynthesis, carbon and nitrogen assimilation.